SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF THIAZOLE DERIVATIVES CONTAINING TRIAZOLE MOIETY USING LiBr AS A CATALYST - Chetna Ameta; Diwaker Sitha; Rajat Ameta; Suresh C. Ameta (Indonesian Journal of Chemistry, 2010)
Synthesis of triazole derivatives from 2-mercaptobenzothiazole has been achieved in four steps under microwave irradiation. LiBr potentially replace solvents and corrosive acids in this reaction scheme. The products of triazole derivatives have shown antimicrobial activity.